2009
DOI: 10.1111/j.1442-2050.2008.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrant promoter methylation ofEDNRBgene in esophageal squamous cell carcinoma

Abstract: Epigenetic silencing of tumor suppressor genes is a major contributor to neoplastic transformation and is an area of intense research. The purpose of the present study was to identify the epigenetic changes in esophageal squamous cell carcinoma (ESCC). Methylation-sensitive arbitrarily primed polymerase chain reaction analysis was used on 21 matched ESCC tumors and adjacent normal tissues. Through this screen we identified a frequently methylated fragment that showed a high homology to the 5' CpG island of end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…During the development of tumor, EDNRB gene transcription is downregulated by promoter hypermethylated, and consequently alters the ET1 signaling pathway [27]. Disruption in the ET1 signaling pathway has been shown to be involved in a variety of human tumor proliferation, angiogenesis, and metastasis [28-30]. EDNRB gene silencing by promoter hypermethylation has been reported in a variety of tumors such as leukemia, oral cancer, skin cancer, head and neck cancer, melanoma, renal cell carcinoma, bladder cancer, and prostate cancer [12-19].…”
Section: Discussionmentioning
confidence: 99%
“…During the development of tumor, EDNRB gene transcription is downregulated by promoter hypermethylated, and consequently alters the ET1 signaling pathway [27]. Disruption in the ET1 signaling pathway has been shown to be involved in a variety of human tumor proliferation, angiogenesis, and metastasis [28-30]. EDNRB gene silencing by promoter hypermethylation has been reported in a variety of tumors such as leukemia, oral cancer, skin cancer, head and neck cancer, melanoma, renal cell carcinoma, bladder cancer, and prostate cancer [12-19].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with 5-aza-2 0 -deoxycytidine (5-Aza-CdR), which is a DNA demethylation agent [15], induces the expression of EDNRB in T24 cancer cells [14]. Silencing of EDNRB expression caused by promoter hypermethylation has also been shown in nasopharyngeal carcinoma, prostate cancer, melanoma, lung cancer, and esophageal carcinoma [16][17][18][19][20]. The high frequency of promoter hypermethylation suggests that downregulation of the EDNRB gene may be involved in human tumorigenesis.…”
Section: Introductionmentioning
confidence: 94%
“…A study has also shown that a dual receptor antagonist inhibited migration of human oesophageal cancer cells in vitro (Jiao et al , 2007). Furthermore, a recent study has identified aberrant promoter methylation of EDNRB gene, which encodes ETBR in humans, in OSCC (Zhao et al , 2009). Although these studies have suggested a potential role of ETBR in OSCC, little is known about its clinical importance.…”
mentioning
confidence: 99%